Co‐culture with peritoneum mesothelial stem cells supports the in vitro growth of mouse ovarian follicles. Issue 12 (6th July 2021) - Sarabadani, Mahdieh; Tavana, Somayeh; Mirzaeian, Leila; Fathi, Rouhollah
Abstract: The important roles played by the ovarian microenvironment and cell interactions in folliculogenesis suggest promising approaches for in vivo growth of ovarian follicles using appropriate scaffolds containing suitable cell sources. In this study, we have investigated the growth of early preantral follicles in the presence of decellularized mesenteric peritoneal membrane (MPM), peritoneum mesothelial stem cells (PMSCs), and conditioned medium (CM) of PMSCs. MPM of mouse was first decellularized; PMSCs were isolated from MPM and cultured and their conditioned medium (CM) was collected. Mouse follicles were separated into four groups: (1) culture in base medium (control), (2) culture in decellularized MPM (DMPM), (3) co‐culture with PMSCs (Co‐PMSCs), and (4) culture in CM of PMSCs (CM‐PMSCs). Qualitative and quantitative assessments were performed to evaluate intact mesenteric peritoneal membrane (IMPM) as well as decellularized ones. After culturing the ovarian follicles, follicular and oocyte diameter, viability, eccentric oocyte percentage, and estradiol hormone amounts were evaluated. Quantitative and qualitative evaluations confirmed removal of cells and retention of the essential fibers in MPM after the decellularization process. Follicular parameters showed that Co‐PMSCs better support in vitro growth and development of ovarian follicles than the other groups. The eccentric rate and estradiol production were statistically higher for the Co‐PMSCs group than for the CM‐PMSCs and control groups. Although the culture of early preantral follicles on DMPM and CM‐PMSCs could improve in vitro follicular growth, co‐culture of follicles with PMSCs showed even greater improvements in terms of follicular growth and diameter.